Volume Estimation of Standing Shorea sp. on UPM-JISE Rehabilitated Forest in Bintulu, Sarawak - Izyan Alwani; Seca Gandaseca (Institut Pertanian Bogor (IPB University), 2008)
This study was aimed to analyze the relationship between diameter at breast height, height, and volume of standing Shorea sp. and the relationship between age and volume of this species. The study was conducted at different ages of rehabilitated forest in Bintulu Sarawak, where the measurement was taken from tree stand year 1992 until 2003. The sampling plot of 20m x 20m was built for each age of stand. Ten standing Shorea sp. were randomly measured for sectionals (taper) from diameter at breast height until the free branches of the tree. The rest of the trees within the plot were only measured by diameter at breast height. All collected data were calculated to find basal area of each tree in meter square (m2). The volume per plot was calculated using the Smalian’s formula to find the taper volume of the Shorea sp. Statistical analysis was conducted to find the regression equation which could explain the relation between volume, diameter, and height of the tree. Result showed that there was a relationship between volume, diameter, and height of the tree, and also there was relationship between volume and age of the tree. Meanwhile, there was no relationship between taper of standing trees and age of trees. This means that volume taper of standing tree and age have no correlation.